EFFECTIVENESS OF SEXUAL EDUCATION FOR TEENAGER’S KNOWLEDGE ON THEIR BODY & SEXUALITY - Cynthia Halim; Bheby Jebriela (Ristekdik : Jurnal Bimbingan dan Konseling, 2020)
Adolescence is a period of transition from children to adulthood. During this stage, generallyteens experience a crisis of identity where they thrive to search for identity, they are no longer children but also not yet full-grown adult. This transition period often brings its own pressure for teens because of the changes they experience either physically, hormonal and even emotionally. The most obvious changes in adolescence is their physical changes in certain body parts that are also related to their sexuality. In Eastern culture, parents are not being able to discuss sexuality openly with their children, therefore teens are reluctant to ask their parents regarding changes in their bodies or even the different feelings they have been experiencing.The purpose of this study was to determine the effectiveness of psychoeducation in adolescents to increase knowledge of church X teenage sexuality. The subjects of this study were church X youth groups, amounting to 21 teens. This research is an experimental study using pretest-posttest group design. Psychoeducation is given as many as 6 (six) sessions which are divided into 2 (two) days.